A Writer's Vision and Creative Process in Retelling the Singapore Story - Kamari, Isa (Malay Literature, 2014)
This paper is a presentation on the vision and creative process of the writer culminating in the production of three novels, namely Memeluk Gerhana (published in English translation as A Song of the Wind), Rawa (Rawa) and Duka Tuan Bertakhta (published in English translation as 1819]). These three novels trace the history of Singapore from the arrival of Raffles on the island up to the 21st century. The aim of the writer was to present an alternative version of history through the retelling of a part of it, and also to present these events something for readers to ponder. Keywords: sense of history, novels, creative process, Memeluk Gerhana, Rawa, Duka Tuan Bertakhta